EKSISTENSI HUKUMAN MATI DITINJAU DARI ASPEK HAM SIPIL DALAM PERSEPEKTIF HAK UNTUK HIDUP - I Gusti Bagus Hengki; I Made Kariyasa; Anak Agung Adi Lestari (Faculty of Law, Mahasaraswati University, Denpasar, 2021)
This scientific paper is expected to find out how the existence of the death penalty is viewed from the aspect of Civil Human Rights in the perspective of the right to life and whether the existence of the death penalty is contrary to the ideology of the Pancasila State and the 1945 Constitution of the Republic of Indonesia and the Human Rights Law with a normative research methodology with using a statutory approach. From the results of the discussion that the existence of the death penalty in terms of the Civil Human Rights aspect in the perspective of the right to life still needs to be maintained, because it does not conflict with the ideology of the Pancasila State and the 1945 Constitution of the Republic of Indonesia, the Human Rights Law, UDHR and ICCPR, as well as religion. in Indonesia, as long as it is not carried out arbitrarily, in accordance with the provisions of the legislation. This needs to be done because to provide protection for individual perpetrators and victims against acts of revenge, emotional, uncontrollable, vigilante, so that it does not guarantee that the death penalty is abolished. Indeed, there are parties who are pro and contra about the death penalty by both underpinning Pancasila, all of which is to make Pancasila a